Indel variants within the PRL and GHR genes associated with sheep litter size. Issue 11 (3rd September 2020) - Akhatayeva, Zhanerke; Mao, Cui; Jiang, Fugui; Pan, Chuanying; Lin, Chunjian; Hao, Kunjie; Lan, Tianxin; Chen, Hong; Zhang, Qingfeng; Lan, Xianyong
Abstract: Growth hormone and prolactin belong to the class of peptide hormones that have a wide range of regulatory functions. In this study, polymorphisms of growth hormone receptor ( GHR ) and prolactin ( PRL ) genes were analysed as candidate genes, which are responsible for the litter size in Australian White (AUW) sheep. According to the statistical analyses results, the polymorphism information content (PIC) values of the PRL‐P1‐ins‐23 bp, GHR‐P2‐del‐23 bp and GHR‐P8‐del‐23 bp were 0.371, 0.366 and 0.375, respectively, which indicates the high genetic polymorphism in AUW sheep. Moreover, all indel loci are not conformed to the HWE ( p < .05). Further, our findings revealed that the PRL‐P1‐ins‐23 bp polymorphism in the ovine PRL gene was significantly related to the first parity litter size ( p = .001) and the DD genotype displaying the highest genotypic mean. Meanwhile, the GHR‐P2‐del‐23 bp and GHR‐P8‐23 bp indels in the ovine GHR gene were significantly correlated with first parity litter size ( p < .05), and the individuals with the genotype II showed significantly higher litter size than others. Collectively, these results demonstrated that our findings could be useful for future sheep breeding strategies based on the molecular‐assisted selection (MAS).